1969
DOI: 10.1002/jctb.5010190107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amorphous silica on the hydration of tricalcium aluminate

Abstract: Amorphous silica influences tricalcium aluminate (C3A) hydration both in pastes and in suspensions. Two heat peaks are found by isothermal calorimetry during the paste hydration of C3A. The addition of amorphous silica causes the second heat peak to shift towards shorter reaction times and become more pronounced. In suspensions, the change in ion concentration in the water phase is not influenced by the presence of amorphous silica except that the change in concentration occurs more quickly. Quantitative X‐ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The effect of nano-SiO 2 on the hydration heat release rate of C 3 A was studied using the isothermal calorimetry, and the results can be seen in Figure 3 . De Jong et al [ 26 ] previously found a second exothermic peak observed in the C 3 A hydration process after adding amorphous silica, which appeared in the first hours of hydration but being at later stage when the amorphous silica content increased. However, as shown in Figure 3 a, this study showed different results.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of nano-SiO 2 on the hydration heat release rate of C 3 A was studied using the isothermal calorimetry, and the results can be seen in Figure 3 . De Jong et al [ 26 ] previously found a second exothermic peak observed in the C 3 A hydration process after adding amorphous silica, which appeared in the first hours of hydration but being at later stage when the amorphous silica content increased. However, as shown in Figure 3 a, this study showed different results.…”
Section: Resultsmentioning
confidence: 99%